Frequency and Patterns of Presentation of Common Types of Odontogenic Tumor at a Tertiary Care Dental Hospital - Rashid, Tania; Chaudhary, Asif Nazir; Aslam, Zeeshan; Akhtar, Fahad (Biological and Clinical Sciences Research Journal, 2025)
Odontogenic tumors, which originate in tissues involved in tooth formation and often develop in the jaw, can be benign or malignant. Objective: To determine the Frequency and Patterns of Presentation of Common Types of Odontogenic tumors at a Tertiary Care Dental Hospital. Methodology: The study, conducted at the Nishtar Institute of Dentistry in Multan, Pakistan, involved 97 patients diagnosed with odontogenic tumors. The research was conducted from September 2023 to September 2024 using a non-probability sequential sampling method. Patients were categorised based on age, gender, and medical reporting. Demographic information was collected, and patients with swellings were assessed through a comprehensive history, clinical examination, and radiographic evaluation. Incisional biopsy was performed for each case. Results: This study assessed 97 participants, comprising 53 males (54.6%) and 44 females (45.4%), revealing a slightly higher prevalence of males in the cohort. The most common odontogenic tumor was ameloblastoma, accounting for 52 cases (53.6%) with a male predominance (30 males vs. 22 females). The regression analysis shows that the presence of fluid on aspiration is associated with a negative correlation (B = -0.351, p = 0.081), suggesting that fluid presence may be linked to a lower occurrence of certain tumors; however, this result was marginally non-significant. Overall, the model does not provide strong predictive value, suggesting that additional factors may contribute to the occurrence of odontogenic tumors. Conclusions: The findings underscore the predominance of ameloblastoma as the most frequently diagnosed odontogenic tumor, particularly in males. The study highlights the varying presentations of different odontogenic tumors, with most being benign and having low metastatic potential, except for a small proportion of ameloblastomas that exhibit aggressive characteristics.